2015
DOI: 10.1016/j.renene.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of concrete mix design on CO2 emissions for large wind turbine foundations

Abstract: a b s t r a c tLarge capacity wind turbines require sizeable foundations. Onshore turbines are commonly supported by massive spread foundations involving hundreds of cubic metres of concrete and tonnes of steel reinforcement. Concrete gravity base foundations for offshore wind turbines also employ significant quantities of concrete and reinforcement. The CO 2 emissions associated with concrete foundations has been analysed to examine means of reducing the materials-related impact on the carbon footprint of win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 25 publications
0
22
0
4
Order By: Relevance
“…Regarding the strength of the materials involved, under the effect of high loads, it has been verified that the increase in the strength of steel significantly reduce CO 2 emissions and is also more advantageous in relation to the proposed indicator that represents the usability of the projected column space. Berndt (2015) in his study used the emission values for Australia to compare the influence of the concrete mixtures on wind turbine plant foundations. The study has shown that, when structurally feasible, the use of smaller resistances is advantageous in relation to CO 2 emissions, provided that other properties, such as durability, are appropriate to the site conditions and the time life.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the strength of the materials involved, under the effect of high loads, it has been verified that the increase in the strength of steel significantly reduce CO 2 emissions and is also more advantageous in relation to the proposed indicator that represents the usability of the projected column space. Berndt (2015) in his study used the emission values for Australia to compare the influence of the concrete mixtures on wind turbine plant foundations. The study has shown that, when structurally feasible, the use of smaller resistances is advantageous in relation to CO 2 emissions, provided that other properties, such as durability, are appropriate to the site conditions and the time life.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
“…Kim et al (2016) If concrete mix and raw material suppliers were carefully selected, it can be obtained a reduction of 34% in the emission of CO 2 and 1% in the costs Park et al (2012) CO 2 emissions increase linearly with the compressive strength of the concrete; to similar strengths, the concrete produced in the winter presented an increase of approximately 5% in the CO 2 emissions Santoro and Kripka (2016) Higher strength concrete will produce a greater amount of CO 2 ; the CO 2 emissions during transport are significant Choi et al (2016) For smaller loads the increase of the transversal area of concrete is more advantageous for the eduction of O 2 emissions, and for greater loads the increase of the steel profile produces a more sustainable solution Berndt (2015) The use of smaller resistances is advantageous in relation to CO 2 emissions; the choice of the concrete mixture strongly influences the magnitude of the CO 2 emissions Yang et al (2015) The intensity of CO 2 emissions gradually decreases as Portland cement is replaced by complementary cementitious materials (up to 20%) García-Segura et al (2014) In comparison to Portland cement, despite the reduction in CO 2 capture and life time, 80% blast furnace slag cement emitted 20% less CO 2 per year Cabello et al (2016) To reduce the environmental impact generated by a structure, the focus should be on phases of production of raw materials, transportation and production of concrete Oliveira et al (2014) It is not appropriate to base decisions on the emissions of concrete solely on the strength of the concrete and the type of cement used, since the variations are significant Paya-Zaforteza et al (2009) Minimization of embedded CO 2 emissions and economic cost seem to be highly related Park et al (2013) Reducing the amount of steel and increasing the amount of concrete can be an effective way to reduce the structural costs and CO 2 emissions of columns Habert and Roussel (2009) It is also possible to combine cement replacement and increase mechanical strength Possan et al (2016) Concrete during its life time can absorb from 40 to 90% of CO 2 emitted in the manufacturing process; the absorption of CO 2 is directly proportional to the surface area of concrete exposed to CO 2 , and influenced by the type of cement and resistance to concrete. Park et al (2014) Increasing the strength of the structural materials used is more efficient in reducing CO 2 emissions and costs than increasing the quantities of structural materials used Collins (2013) If carbonation is ignored, emission estimates can be overestimated by up to 45% depending on the strength of the concrete that was used as well as the type of construction application that incorporates recycled concrete during the second generation Yepes et al (2012) CO 2 emissions and costs are closely related.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
“…The two primary performance variables are the grade and density of the concrete. The concrete mix designs were collected from 8 published journal papers and databases [51][52][53][54][55][56][57][58][59]. These mix designs represent some conventional (normal weight) and some advanced methods of concrete admixture [52,54,56,57] that gives lightweight and ultra-lightweight concrete.…”
Section: -1 Materials and MIX Designsmentioning
confidence: 99%
“…Observa-se que o valor de emissões de CO2 dos RSCD provenientes da empresa estudada foi inferior ao valor de Santoro e Kripka (2016) e superior ao valor apresentado por Rossi (2013), estando entre valor apresentado por Oliveira et al (2013b), igual a 1,8 kgCO2/t, e Berndt (2015), igual a 4,0 kgCO2/t, feita a partir da mistura dos outros materiais, em proporções exatas. Esse produto é bastante comercializado para obras de pavimentação (Figura 7).…”
Section: Avaliação Das Emissões De Co2unclassified